Acquiring Information through Peers - Herskovic, Bernard; Ramos, João (American Economic Review, 2020)
We develop an endogenous network formation model, in which agents form connections to acquire information. Our model features complementarity in actions as agents care not only about accuracy of their decision-making but also about the actions of other agents. In equilibrium, the information structure is a hierarchical network, and, under weakly convex cost of forming links, the equilibrium network is core-periphery. Although agents are ex ante identical, there is ex post heterogeneity in payoffs and actions. (JEL D83, D85, Z13)